PEMBELAJARAN BAHASA BALI KESULITAN DAN SOLUSINYA - ADNYANA, I KETUT SUAR (Widya Accarya, 2013)
Learning Balinese leads to mastering language theory, literature theory, and four language skills.To reach these objectives are influencedby many factors among others: choosing method of teaching, language attitude of language community (students). Based on the analysis conducting on learning process in elementary school on the fifth and sixth year, there is indication that students find difficulties in learning Balinese. The difficulties can be analyzed from mastering four language skills. The difficulties are caused by there is no variation of teaching method, and language attitude of student.